An approach to determine brittle upper crustal thinning: Insights into crustal extension discrepancy in the central part of Qiongdongnan Basin - He, Chao; Zhao, Zhongxian; Lee, Eun Young; Xue, Yulong (Frontiers in Earth Science, 2023)
Summing fault heaves is the most commonly used method to evaluate upper crustal thinning. However, since fault deformation width (W) is often assumed as a constant in the range of 75 to 150 km, the stretching factor estimated from fault geometry (βf) accompanies significant uncertainty. Here we propose a new approach to determine brittle extension factors on the foundation of numerical analyses of W and further compare our results to previous methods, with specific reference to the central part of Qiongdongnan Basin, South China Sea (SCS). Our results suggest that the value of W is generally less than 80 km and mostly less than 50 km in the northern SCS margin. We confirm that applying an overestimated value of W can lead to an underestimated amount of fault-related extension and overstatement of extension discrepancy in the rifted margin. Results also indicate an inverse discrepancy with our new method in the southeast of the basin. The difference in syn-rift sediment thickness across the rifted margin likely drove the lower crust flow causing a transition between inverse and positive extension discrepancies.